PEMBELAJARAN PENDIDIKAN JASMANI ADAPTIF BERBASIS MUSIK DAERAH PADA SENAM AEROBIK - Fauqi, Amal (Jurnal Ilmiah Mandala Education (JIME), 2022)
Research has been carried out on the Development of Adaptive Physical Education Learning Devices on the material of Aerobic Gymnastics Based on Local Culture "Rawa Mbojo Mantoi" Using the Project Based Learning (PJBL) Model to Develop Creativity in Students of the Physical Education Study Program STKIP Yapis Dompu. This study seeks to teach students to be able to prepare themselves to become Physical Education Teachers, take an attitude and train creative thinking skills with a special needs-based learning approach (ABK). This research method is development research using a 4-D model consisting of several steps, namely: a) define, b) design, c) develop, and d) dissemination. The learning model used in this research is Project Based Learning (PJBL) with the stages: 1) determining the basic questions, 2) designing project plans, 3) developing schedules, 4) monitoring project progress, 5) testing learning processes and outcomes, 6) experience evaluation. The conclusion obtained from this research is that the cumulative value of the two validators for all components of the learning device developed is in the very valid category with a score of 3.6. Details of the 4 components of the equipment assessed include: RPS with a score of 3.8/very valid, MFI with a score of 3.3/valid, Textbooks with a score of 3.6/valid, KBK test with a score of 3.7/very valid. Thus, all components of the learning tools that have been developed are feasible to use and try out.